1999
DOI: 10.1083/jcb.145.1.29
|View full text |Cite
|
Sign up to set email alerts
|

A Nonerythroid Isoform of Protein 4.1R Interacts with the Nuclear Mitotic Apparatus (NuMA) Protein

Abstract: Red blood cell protein 4.1 (4.1R) is an 80- kD erythrocyte phosphoprotein that stabilizes the spectrin/actin cytoskeleton. In nonerythroid cells, multiple 4.1R isoforms arise from a single gene by alternative splicing and predominantly code for a 135-kD isoform. This isoform contains a 209 amino acid extension at its NH2 terminus (head piece; HP). Immunoreactive epitopes specific for HP have been detected within the cell nucleus, nuclear matrix, centrosomes, and parts of the mitotic apparatus in dividing cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
153
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(162 citation statements)
references
References 75 publications
6
153
0
Order By: Relevance
“…In keeping with the key transitions in the cell cycle controlled by the cyclin-dependent kinases, the redistribution of 4.1R to the mitotic spindle and spindle poles is regulated by a phosphorylation event that occurs at Thr-60 and Ser-679 sites by cyclin-dependent cdc2 kinase. 2 We (20) previously showed that a 135-kDa 4.1R isoform may participate in mitosis via its association with the non-centrosomal proteins NuMA, dynein, and dynactin, which are essential to the organization of functional spindle poles and tethering of the centrosomes to the spindle pole (21). From these results, we hypothesize that 4.1R plays an important role in organizing mitotic spindle and spindle poles.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…In keeping with the key transitions in the cell cycle controlled by the cyclin-dependent kinases, the redistribution of 4.1R to the mitotic spindle and spindle poles is regulated by a phosphorylation event that occurs at Thr-60 and Ser-679 sites by cyclin-dependent cdc2 kinase. 2 We (20) previously showed that a 135-kDa 4.1R isoform may participate in mitosis via its association with the non-centrosomal proteins NuMA, dynein, and dynactin, which are essential to the organization of functional spindle poles and tethering of the centrosomes to the spindle pole (21). From these results, we hypothesize that 4.1R plays an important role in organizing mitotic spindle and spindle poles.…”
mentioning
confidence: 71%
“…Antibody Production-Antisera to synthetic peptides of exon 13 of 4.1R (DSADRSPRPTSAPAI) (anti-exon 13) and the recombinant HP of 4.1R (anti-HP) were prepared as described previously (20). The sera were purified on immunoaffinity columns using the Sulfolink kit (Pierce) covalently cross-linked to the synthetic peptides or fusion peptides used for immunization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4.1B contains a putative nuclear localization signal (NLS) (KRRK), as well as an upstream casein kinase II site (SAAE), a common feature in proteins containing an NLS (Kittiniyom et al, 2004). Furthermore, 4.1B has been shown to translocate from the plasma membrane into the nucleus in PC12 cells following differentiation (Gascard et al, 2004), and the 4.1 family members merlin, ezrin, and 4.1R localize within the nucleus under some conditions (Mattagajasingh et al, 1999;Batchelor et al, 2004;Muranen et al, 2005). To exclude the possibility that the observed nuclear localization of 4.1B was due to nonspecific staining by the 4.1B antibody, we created a GFP-4.1B fusion construct (pEFGP-4.1B) in order to monitor the localization of the exogenous protein without having to rely on the antibody.…”
Section: Erm Proteins Are Downregulated During Pregnancymentioning
confidence: 99%